Un os de vautour dans la basse cour du château de Broue (xive siècle, Saint-Sornin, Charente-Maritime) - Maude Barme; Benoît Clavel (Archéologie Médiévale)
The recent discovery of a black vulture bone on the castle of Broue (14th century, France, Charente-Maritime) raises questions about the possible use of this bird. We will also discuss the possibility of this particular bird trade during the Middle Ages. The authors have inventoried medieval and modern discoveries of the remains of monk vultures in archaeological contexts. They discussed the use of feathers and the exploitation of the bird’s carcass. They also discussed the possibility of the existence of captive animals. This contribution, based on the examination of archaeozoological and textual sources, attempts to define the status of the vulture, in general, and the monk vulture, in particular, in medieval and modern times.